Increased Rates of Donation With Laparoscopic Donor Nephrectomy - Schweitzer, Eugene J. (2000)
OBJECTIVE: To examine the impact of laparoscopic nephrectomy and recipient education on the proportion of kidney recipients who could identify a potential live donor, and on the live donor (LD) transplantation rate. SUMMARY BACKGROUND DATA: Laparoscopic donor nephrectomy (LDN) results in less postoperative surgical pain, a shorter hospital stay, and quicker recovery than the standard open donor nephrectomy (ODN). The authors hypothesized that the availability of this less invasive surgical technique would enhance the willingness of family and friends to donate. METHODS: The study population consisted of 3,298 end-stage renal disease patients referred for kidney transplant evaluation between November 1991 and February 2000, divided into three groups. The first group received no formal LD education and had only ODN available. The second group received formal education about the LD process and had only ODN available. The third group had both formal LD education and LDN available. Records were examined to determine what proportion of each group had any potential donors tissue-typed, and the rate at which they received an LD transplant. RESULTS: Before LDN availability and formal LD education, only 35.1% of referrals found a potential donor, and only 12.2% received an LD transplant within 3 years. Institution of a formal education program increased the volunteer rate to 39.0%, and 16.5% received an LD transplant. When LDN became available, 50% of patients were able to find at least one potential donor, and within 3 years 24.7% received an LD transplant. Regression analysis indicated that availability of LDN was independently associated with a 1.9 relative risk of receiving an LD transplant. Kaplan-Meier death-censored 1- and 3-year graft survival rates for ODN transplants were 95.8% and 90.6%, versus 97.5% and 94.8% for LDN. CONCLUSIONS: The availability of LDN and an LD family education program has doubled the live donor transplantation rate, and outcomes remain excellent.